5-HT receptor-mediated modulation of granule cell inhibition after juvenile stress recovers after a second exposure to adult stress. (7th May 2015) - Gruber, D.; Gilling, K.E.; Albrecht, A.; Bartsch, J.C.; Çalışkan, G.; Richter-Levin, G.; Stork, O.; Heinemann, U.; Behr, J.
Highlights: Investigation of single versus combined stress in two-hit stress model. Serotonergic modulation of GABAergic transmission reduced after single stress. Significant effect on mRNA levels of CCK+ cell markers after single stress. Serotonergic effects after single stress recover after combined stress. Abstract: Aversive experiences in early life are thought to dispose to psychopathologies such as mood or anxiety disorders. In a two-hit stress model, we assessed the effects of juvenile and/or adult stress on the 5-HT-mediated modulation of synaptic inhibition of ventral dentate gyrus granule cells. Combined but not single stress exposure led to a significant reduction in activity and increased anxiety-like behavior. Similarly, the 5-HT1A receptor-mediated inhibition of evoked inhibitory postsynaptic currents (IPSCs) of granule cells was only reduced in single stress exposed animals. This was also true for the number of granule cells responding with a 5-HT3 receptor-dependent burst of miniature IPSCs. 5-HT3 receptors are expressed on cholecystokinin (CCK)+ basket cells in the hippocampus. In fact, we observed a reduction of steady-state mRNA levels of CCK+ basket cell markers after single juvenile or adult stress and partial recovery after combined stress, thus matching the electrophysiological findings. Adaptive changes in 5-HT-mediated modulation of synaptic inhibition and CCK+ basket cells in the DG may help to maintain normal levels of anxiety after single juvenile or adult stress exposure, as indicated by the increased anxiety that accompanies the loss of this regulation upon combined stress.